Quantum Theory: A Very Short Introduction - Polkinghorne, John (New York Oxford University Press, 2002)
In simple language, without mathematics, this book explains the strange and exciting ideas that make the subatomic world so different from the world of the every day. It offers the general reader access to one of the greatest discoveries in the history of physics and one of the oustanding intellectual achievements of the twentieth century.
Includes Index and Illustrations.
Keywords: Quantum theory